Do financial results influence sports results in football industry? – Case study of the Brazilian football league - Tertuliano, Ivan Wallan; Lima, Eric Matheus Rocha; de Oliveira, Vivian; Pavlović, Vladan D; Machado, Afonso Antonio; Fischer, Carlos Norberto (Industrija, 2018)
The purpose of this article is to investigate the influence of club revenues on their classification during the seasons from 2007 to 2016 of the first division of the Brazilian Football League. The data on club revenue and classification presented in this study were obtained on the websites of the clubs, of entities that investigate the sports economy of the Brazilian Football Confederation. In this study, we used information from 16 clubs, which were divided into 3 sample groups, according to the Total Revenue in dollars. The results showed that the G1 group had higher total revenue than the other groups and that the G3 Group had the lowest revenue among the groups, but that all groups evolved during the evaluated years. In relation to the classification, you can see that groups G1 and G2 presented similar results and that the G3 group always occupied the lowest ranked places in the championship. These results demonstrated a correlation between revenue and club classification. These results allow us to conclude that the higher- revenue teams showed better positions in the championship because, by collecting more, they tend to have better conditions to compete for the title and continue to increase their revenues, not only for awards and sponsorships, but also for exploring their titles.
Keywords: Revenue; Football; Classification; Brazilian